Pengaruh Model Pembelajaran Quantum Teaching terhadap Keterampilan Menulis Teks LHO SMKN 3 Kediri: The Influence of the Quantum Teaching Learning Model on the Writing Skills of LHO Texts at SMKN 3 Kediri - Laras Dwi Jayanti; Andri Pitoyo; Nur Lailiyah (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to determine the effect of the use of the Quantum Teaching learning model on the skills of writing observational report texts of class X students of SMK Negeri 3 Kediri. This study is an experimental study using a pretest-posttest group design, namely a research design involving two class groups, namely the experimental group and the control group. The research population was all class X students of SMK Negeri 3 Kediri in the 2025/2026 academic year. The research sample was taken randomly with a total of 70. The data collection instrument for this study was a performance test in the form of practice writing observational report texts. Data analysis techniques were carried out using normality tests and homogeneity tests, and t-tests. The results showed that the average pretest score of the control class was 56.14, then after being treated with the STAD learning model, the average posttest score increased to 69.97. While the average experimental class score was 56.49, then after being treated with the Quantum Teaching learning model, the average posttest score increased to 83.26. The results of the inferential statistical analysis showed that the t-count value of 11.130 was greater than the t-table of 1.995 at a significance level of 5% and df = 68. In addition, the contribution of the Sig. (2-tailed) value of 0.000 <0.05 was also found, which indicated a significant influence between the use of the Quantum Teaching learning model and the STAD learning model on the skills of writing observational report texts. Thus, the results stated that Ha was accepted and Ho was rejected.